«Islamic Socialism» in Pakistan: Evolution, Implementation and Legacy in Domestic and Foreign Policy - G. G. Makarevich (Vestnik MGIMO-Universiteta)
The article examines the phenomenon of "Islamic socialism" in Pakistan and its impact on the nation's current domestic and foreign policies. Employing critical theory, the author delves into an analysis of the political class's objectives and how the environmental context influenced the political process, offering insights into the perceptions held by higher echelons. The application of elite theory allows for a deconstruction of the Pakistani statehood, unveiling the specific social groups shaping developmental trajectories. By leveraging historical sociology in international relations, the article investigates the influence of historical underpinnings on the decision-making of social groups, shedding light on their endeavors to construct the past for political purposes.The study meticulously traces the origins of "Islamic socialism," exploring the discourse's evolution in the initial decades following the country's independence. It identifies the driving forces that led the state leadership to adopt the model of "Islamic socialism." Focused on the tenure of Zulfiqar Ali Bhutto (1971-1977), the article examines the implementation of the "Islamic socialism" policy and the subsequent reasons for its failure, culminating in a military coup. The author contends that the principles of "Islamic socialism" introduced in Pakistan's domestic and foreign policy retained relevance even after its rejection.Conclusively, the article posits that the "Islamic socialism" constructed by Pakistani elites, often viewed through an orientalist lens, emerged not only as a response to the crisis in Pakistani statehood but paradoxically, became a crucial driver in shaping Islamabad's foreign policy determinants. Notably, this development forged integral relationships with China and the Islamic world, evolving into pivotal imperatives in Pakistan's grand strategy.This study highlights the interplay between "Islamic socialism," the crisis in Pakistani statehood, and its unforeseen impact on foreign policy, ultimately forming the bedrock for Islamabad's strategic engagements with China and the Islamic world.